Penerapan Project Based Learning (PjBL) Untuk Meningkatkan Kreativitas Siswa Kelas X Pada Materi Pemetaan Di SMA Negeri 1 Botumoito - Hauko, Riski; Lihawa, Fitryane; Masruroh, Masruroh (Jurnal Pendidikan Geografi Undiksha, 2025)
Creativity is defined as a person's ability to create something new, which is the result of a series of discoveries that enable a person to think creatively. This research aims to show whether there is an increase in the creativity of class This type of research is classroom action research. Based on the research results, it was found that an increase in students' creativity in cycle I and cycle II in the application of the Project Based Learning (PjBL) model was obtained for cycle I, 45% in the poor category. This is because students have not been able to develop their creative ideas in making maps. In cycle II the score was 95% in the good or optimal category. Increasing student creativity optimally shows that teachers are trying to improve the quality of learning, which can be seen from increasing student creativity. The research results show that the application of the Project Based Learning (PjBL) model can increase the creativity of class X-1 students in Mapping material at SMA Negeri 1 Botumoito.